Exploring the association between social media disorder and academic procrastination of college students: The mediation role of intrusive thinking and fatigue - Choudhury, Sourav; D'Cruz , Nikita Ruth; Deb , Joy Prakash; Biswas , Samiul; Patil, Sandeep (Journal of Interdisciplinary Studies in Education, 2024)
The study aimed at exploring the relationship between social media disorder and academic procrastination, and to thereby investigate the mediating effects of intrusive thinking and fatigue. By enrolling 412 undergraduate college students in India, the interconnectedness of the four variables was investigated using Social Media Disorder scale by Choudhury et al. (2024), White Bear Suppression Inventory by Rassin (2003), Fatigue Assessment Scale by Michielsen et al. (2003) and Academic Procrastination Scale by Mccloskey and Scielzo (2015). The results disclosed: 1) A significant gender differences in the level of SMD; 2) Correlation analysis displayed a significant positive correlation between the four variables; 3) The multiple mediating effect test results showed that SMD caused academic procrastination directly and indirectly through three pathways.